Analysis of microbiological and chemical qualities of vacuumed and unvacuumed mirror carp (Cyprinus carpino L.) Pastrami - Arslan, Ali; Çelik, Cernai; Gönülalan, Zafer; Ateş, Gülsüm; Kök, Filiz; Kaya, Aysel (Scientific and Technical Research Council of Turkey, 1997)
The aim of this study was to produce fish pastrami from Cyprinus carpio. Matured pastrami samples were vacuumed in PVC plastic bags. Vacuumed and unvacuumed samples were stored in refrigerator (+4°C) and analysed for microbiologic and chemimcal properties at 0, 7, 14, 21, 30, 45, 60, 90 and 120th days. Impact of vacuum was determined according to the results of microbiologic and chemical analysis. In microbiologic analysis of viable aerobes, anaerob microorganisms, psychrophiles, Lactobacillus, Micrococcus - Staphylococcus, yeast and molds in vacuumed pastrami were between 8.1 × 104 - 9.6 × 105 cfu/g; 2.2 × 104 - 1.2 × 105 cfu/g; 3.6 × 102 - 7.6 × 104 cfu/g; 11 - 3.8 × 104 cfu/g; 5.5 × 103 - 1.6 × 105 cfu/g; 25 - 5.2 × 102 cfu/g and in unvacuumed pastrami were between 1.0 × 104 - 6.2 × 105 cfu/g; 7.6 × 102 - 4.6 × 105 cfu/g; 11 - 2.1 × 103 cfu/g; 6 - 6.3 × 103 cfu/g; 93 - 4.4 × 103 cfu/g respectively. Coliforms were not found in both vacuumed and unvacuumed pastrami samples. Yeast and molds were not observed in pastrami samples stored in unvacuumed environment. Moisture, protein, fat, ash and salt content, pH and TVB values in vacuumed pastrami were between 23.06 - 30.98%; 55.24 - 62.32%; 4.55 - 10.64%; 5.29 - 8.65%; 6.92 - 10.50%; 5.58 - 6.0; 17.35 - 18.65 mg/100 g in pastrami and in unvacuumed pastrami were between 15.19 - 39.17%; 39.53 - 61.11%; 6.48 - 21.59%; 5.05 - 12.87%; 7.25 - 12.31%: 5.67 - 6.27; 15.04 - 19.51 mg/100 g respectively. Statistically, the differences in viable aerobes on 21, 30, 90. 120th; anaerob microorganisms on 0, 21, 45, 60, 90, 120th; psychrophiles on 30, 45th; Micrococcus - Staphylococcus on 0, 7, 14, 60, 90, 120th days of maturity were significant also differences on numbers of yeast and molds were significant in all peridos. However, differences in values on 0, 14, 21, 60, 90, 120th days for moisture; 0, 7, 14, 21, 30, 90, 120th days for protein; 0, 7, 14, 30, 90, 120th days for fat; 14, 60, 90, 120th day for ash; 21, 30, 45, 60, 120th days for salt content and 21, 30, 60, 90th days of maturity for pH were significant (p<0.05). Total yield rate in all fish pastrami samples was 49.35%.
Vakumlu ve Vakumsuz Aynali Sazan (Cyprinus carpio L.) Pastirmalarinin Mikrobiyolojik ve Kimyasal Kalitesinin incelenmesi
Keywords: Chemical; Fish pastrami; Microbiological; Quality; Unvacuumed; Vacuumed